Analysing the Local Communities' Perception on the Economic and Environmental Factors of Ecotourism in Tagang System Framework: The Case of Semedang Village, Sarawak, Malaysia - Nur Zaimah, Ubaidillah; Rossazana, Ab-Rahim; Sutera, Jul; Nor Afiza, Abu Bakar; Salbiah, Edman; Rosita, Hamdan (Human Resource Management Academic Research Society (HRMARS), 2018)
Ecotourism is a natural product that plays a role in enhancing the economy of a country. Tagang system is a new tourism product that contributes to a more efficient environmental management, contributing to economic development, and social development of communities. The objective of this study was to identify the factors that influence the development of Tagang system in ecotourism framework at Semedang village. A total of 63 surveys were collected using random sampling method. Data were analysed using the reliability test and factor analysis. The results showed that there are four contributing factors of Tagang system in the Semedang village which are economic development, conservation of the natural area, awareness of Tagang advantages and biodiversity management.